A case of information technology and information seeking behaviour among managers - Halimah Badioze Zaman,; Norhayati A. Mukti,; Zuraidah Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 1999)
This paper highlights a case study carried out in a rubber-based medium-sized manufacturing company on the information seeking behaviour and use of information technology (IT) of its 30 top and middle level managers. The theoretical model developed in this study can be used as initial groundwork for future studies in information seeking behaviour of managers generally and Malaysian managers specifically. Generally, results of the study showed that managers relied on both internal and external information. Findings of the study also showed that there was a correlation between the functional role of managers and their IT and information seeking behaviour patterns. An interesting findings was that the managers would rely more on informal seeking patterns rather than computerized information seeking patterns